PREVALENCE OF URINARY TRACT INFECTION IN CHILDREN PRESENTING WITH DIARRHEA (The Research of Medical Science Review, 2025)
Background: Urinary tract infections (UTIs) are common in children and can lead to significant morbidity, particularly if not diagnosed and treated promptly. Diarrhea, a frequent pediatric condition, may complicate the clinical presentation of UTIs. Objective: This study aimed to investigate the prevalence of UTIs in children presenting with diarrhea at The Children’s Hospital and UCHS, Lahore. Methods: A cross-sectional study was conducted on 86 children aged 6 months to 12 years who presented with diarrhea at the Emergency Department of The Children’s Hospital and UCHS, Lahore. Data were collected through non-probability consecutive sampling. A clean-catch midstream urine sample was collected from each child and sent for culture analysis. Results: Of the 86 children, 30.2% tested positive for a UTI. The highest prevalence was observed in children under 5 years of age (37.5%), and moderate diarrhea was associated with the highest UTI prevalence (40%). The most common pathogen identified was Escherichia coli (61.5%), followed by Klebsiella pneumoniae (19.2%) and Proteus mirabilis (11.5%). Gender did not show a significant association with UTI prevalence, but age and diarrhea severity were significant factors. Conclusion: It is concluded that UTIs are prevalent in children with diarrhea, particularly in younger children and those with moderate to severe diarrhea. Clinicians should maintain a high index of suspicion for UTIs in such patients to ensure timely diagnosis and treatment, thereby preventing potential complications such as kidney damage.